Outcomes and impact of device iterations in mitral valve transcatheter edge-to-edge repair: the REPAIR study - Stein, Philipp von; Stolz, Lukas; Haurand, Jean Marc; Gröger, Matthias; Rudolph, Felix; Mustafa, Donika; Jobst, Jannik; Mues, Christoph Alexander; Mahabadi, Amir Abbas; Hörbrand, Isabel; Schulz, Carl; Sugiura, Atsushi; et al. (JACC Cardiovascular interventions, 2025)
Background - The PASCAL P10 system for mitral valve transcatheter edge-to-edge repair has undergone iterations, including introduction of the narrower Ace implant and the Precision delivery system. - Objectives - This study sought to evaluate outcomes and the impact of PASCAL mitral valve transcatheter edge-to-edge repair device iterations. - Methods - The REPAIR (REgistry of PAscal for mltral Regurgitation) study is an investigator-initiated, multicenter registry including consecutive patients with mitral regurgitation (MR) treated from 2019 to 2024. Patients were stratified by device iteration: P10only, P10/AceGen1 (introduction of Ace), and P10/AcePrec (introduction of Precision). The primary endpoint was MR ≤1+ at discharge; secondary endpoints included technical success and MR durability (discharge vs 30 days, 1 year, and 2 years). - Results - A total of 2,165 patients (mean age 78 ± 10 years, 44% female, 85% in NYHA functional class ≥III, EuroSCORE II [European System for Cardiac Operative Risk Evaluation II] 4.9% [Q1-Q3: 3.0% to 8.1%]) were included: 660 P10only, 945 P10/AceGen1, and 560 P10/AcePrec. Median follow-up was 510 days (Q1-Q3: 369-874 days). Primary (47% [n = 1,019 of 2,142]) and secondary (52% [n = 1,123 of 2,142]) MR etiology did not change across device iterations (P = 0.547). Technical success was achieved in 97.0% (n = 2,099 of 2,165) with similar rates across device iterations (P = 0.290). MR ≤1+ was achieved in 72% (n = 1,397 of 2,085), improving with device iterations (P10only: 66% [n = 422 of 638], P10/AceGen1: 73% [n = 661 of 906], P10/AcePrec: 77% [n = 414 of 541]; P < 0.001). MR grades of ≤1+ and ≤2+ slightly worsened at 30 days, 1 year, and 2 years, primarily in patients with primary MR, with no differences across iterations. - Conclusions - Device iterations of the PASCAL system resulted in increasing rates of achieving MR reduction to ≤1+ at discharge, with stable and high technical success rates. A slight deterioration of the initial result warrants further investigation.